A novel constitutive model for multi-step stress relaxation ageing of a pre-strained 7xxx series alloy. (July 2018) - Zheng, Jing-Hua; Lin, Jianguo; Lee, Junyi; Pan, Ran; Li, Chen; Davies, Catrin M.
Abstract: A novel set of unified constitutive equations has been developed and validated to describe stress relaxation ageing (SRA) behaviour of 7xxx series aluminium alloys. The model, based on dynamic ageing and power-law creep relations, can predict the stress relaxation, age hardening response and their interactions at different temperatures, through considering the microstructure evolutions (precipitate radius, volume fraction and dislocation density) during SRA. In addition, the model newly incorporates the effects of prior plastic strain. This model was verified through T74 multi-step SRA experiments for different pre-strain conditions. Excellent agreement was achieved between the predicted and experimental results for stress relaxation and yield strength variation. The evolution of micro-internal variables (e.g. normalised precipitate radius) within the model were calibrated by observing transmission electron microscopy (TEM) images both performed in this work and available in literature. The advanced constitutive model developed predicts the mechanical properties and residual stresses in components after ageing. Therefore, the model provides a valuable tool to optimise manufacturing processes leading to many benefits including reduced scrap rates and financial losses. Highlights: A novel constitutive model for stress relaxation ageing behaviour of 7xxx series aluminium alloy was developed. Constitutive equations were based on the interactions between stress relaxation and dynamic age hardening. Model was calibrated with experimental test data. Model can predict multi-step stress relaxation and yield strength evolution during stress relaxation ageing for different pre-strain levels.